(untitled) - Seward, Jack (Tokyo, Japn, 1988)
This books consists of the following manay parts: first acquaintance with the Japanese, land of the ripe rice ears, hot springs and baths, can humor survive translation, colorful ways of departing this world, crime and punishment in two countries, matters sexual, japanese views of the West, a museum of religion...
Keywords: National characteristics, japanese